Atlas anatomi untuk umum dan mahasiswa kedokteran, termasuk perawat, bidan, ahli kecantikan Chr. P. Raven ; penerjemah oleh Ahmad Ramali, Hendra T. laksman ; ilustrasi, Louise H. Blumenthal - RAVEN, Chr. P; Ramali, Ahmad; Laksman, Hendra T; Blumenthal, Louise H (Djambatan, 1981)
48 hlm ilus 32 cm